1993
DOI: 10.1111/j.1365-246x.1993.tb03922.x
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Tidal Variations In the Length of Day

Abstract: S U M M A R YObservations of the length of day, corrected for the effects of variations in the angular momentum due to changes in wind velocity and atmospheric pressure, ocean-tide heights and currents, and solid-Earth zonal tides, were analysed. The (1992) IERS Standards model for the effects of zonal tides on the Earth's rotation, which includes ocean-tidal effects, adequately accounts for the observations of the high-frequency (periods between one and 30 days) variations in the length of day at the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Brosche et al (1991) report general agreement between the Brosche et al (1989) fortnightly ocean tidal predictions and recent VLBI UT1 data. McCarthy & Luzum (1991) find that the bulk of the power in long-period 1.o.d. observations (from a combined VLBI, SLR, and LLR data set) can be accounted for when the entire Brosche et al (1989) long-period model (as well as atmospheric angular momentum effects) are incorporated into the standard set of UT1 corrections.…”
Section: Comparisons With Observationsmentioning
confidence: 97%
“…Brosche et al (1991) report general agreement between the Brosche et al (1989) fortnightly ocean tidal predictions and recent VLBI UT1 data. McCarthy & Luzum (1991) find that the bulk of the power in long-period 1.o.d. observations (from a combined VLBI, SLR, and LLR data set) can be accounted for when the entire Brosche et al (1989) long-period model (as well as atmospheric angular momentum effects) are incorporated into the standard set of UT1 corrections.…”
Section: Comparisons With Observationsmentioning
confidence: 97%
“…Several studies in the past have attempted to estimate k or k/C from observations of UT1 using a variety of observing techniques including classical optical, satellite laser ranging, and VLBI ob•servations [Pil'nik, 1970;Guinot, 1970;Guinot, 1974;Djurovik, 1976;Hefty, 1982;Capitainc and Guinot, 1985;Merriam, 1985;Luo et al, 1987;Newhall et al, 1988;Robertson et al, 1988;$chuh, 1988;Pejovi6 and Vondrdk, 1989;Hefty and Capitainc, 1990;Nam and Dickman, 1990;Brosche et al , 1991;McCarthy and Luzum, 1993]. This paper reports the results of our analysis of 9 years of VLBI UT1 values.…”
Section: Discussion Of the Problemmentioning
confidence: 99%
“…Analogous plots are done for the imaginary part κ im in Figure 2. As shown more than two decades ago (Chao et al, 1995;Defraigne & Smits, 1999;McCarthy & Luzum, 1993;Merriam, 1984), the error bars and the dispersion are strikingly squeezed by considering the atmospheric correction (case 2/4). The improvement resulting from the additional ocean correction can be noticed for the real part at many tidal periods, where oceans bring the estimated value toward the mean (13.78 days,MSf,27.44 days,27.68 days,MSm,Ssa) despite a large uncertainty for some waves.…”
Section: Table 2 Estimated Admittances For the Lod (Space Series) Cor...mentioning
confidence: 95%
“…In the 1990's, thanks to VLBI observations, the LOD was determined with a precision of about 0.02 ms. Removing the atmospheric correction from LOD, McCarthy and Luzum (1993) concluded that dynamical ocean tides, as modeled by Dickman (1993) or Wuensch and Busshoff (1992), are more relevant than equilibrium ones for calculating the LOD oscillations at zonal tide periods, and Chao et al (1995) determined the admittances of 11 zonal tides between 2 and 35 days with an uncertainty smaller than 0.05. In order to account for these progresses, Defraigne and Smits (1999) slightly improved the model of Yoder and Williams (1981), addressing a three layered Earth (an anelastic inner core, an inviscid fluid core and an anelastic mantle) and the dynamical effect of the ocean tides.…”
Section: 1029/2021jb022962mentioning
confidence: 99%
See 1 more Smart Citation